ETHICAL AND AESTHETIC ANALYSIS OF SOCIO-CULTURAL CHANGES BASED ON THE VIEWS OF IMMANUEL KANT - Bozarova F.G. (Uzbekistan Open Conference, 2025)
This article provides a philosophical analysis of the ethical and aesthetic views of Immanuel Kant. Research and understanding of events and processes, laws, contradictions, and trends in the development of cultural existence provide an opportunity for a deep understanding of the essence of human morality.
Keywords: beauty; sublimity; morality; culture; cultural transformation; art; genius; mass culture; trends in development